α1-Adrenoceptor subtypes mediating the norepinephrine-induced contractile response in the rat vas deferens - Queiroz-Neto, Antonio; Ballejo, Gustavo (Elsevier, 1993)
1. The effects of chlorethylclonidine (CEC), 5-methyl-urapidil (5-MU), ryanodine and prolonged exposition to norepinephrine (NE) on the concentration-response curves (CRC) to this agonist on the bisected rat vas deferens (RVD) were investigated. 2. CEC did not affect the 50% effective concentration (EC50) of NE in either the prostatic (PP) or the epididymal (EP) portions of the RVD. 3. 5-MU did not alter the EC50 of NE in the PP but caused a significant and concentration-dependent rightward shift of the CRC to NE in the EP. 4. Ryanodine caused a shift to the right of the CRC to NE in the PP associated to a decrease in maximal response, but did not affect the CRC to NE in the EP. 5. Incubation of the EP with NE for 6 hr elicited a significant decrease in the maximal response with no changes in the EC50. Similar treatment of the PP was associated with a significant shift to the right of the CRC to NE without modifications in the maximal response. 6. These results suggest that in the RVD, NE interacts with two different α1-adrenoceptors subtypes which are disposed in a selective manner along the RVD: the α1a subtype in the EP, and a non-α1b-non-α1a adrenoceptor subtype mainly located at the PP. © 1993.